The Effectiveness of the Service Learning Method on Pre-Disaster Preparedness in Undergraduate Midwifery Students at STIKES RSPAD Gatot Soebroto - Christin Jayanti; Widya Rahayu (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Background:Indonesia is a country with a high level of disaster risk so that disaster preparedness is an important competency for health workers, including midwifery students as prospective midwives. One of the learning methods that can be used to improve pre-disaster preparedness is Service Learning. Objective: This study aims to analyze the effectiveness of the Service Learning learning method on the knowledge and attitudes of pre-disaster preparedness in the Undergraduate Midwifery Study Program students of STIKes RSPAD Gatot Soebroto. Method: This study used a quasi-experimental design with a pretest-posttest control group design approach. The research sample was 60 using a total sampling technique. Results: The average student knowledge score increased from 78.33 ± 16.681 before the intervention to 99.42 ± 2.015 after being given the Service Learning learning method. The average attitude score increased from 72.45 ± 14.168 to 86.37 ± 1.650. The Wilcoxon test results showed a significant difference in knowledge (p = 0.000) and attitude (p = 0.001) before and after the intervention. Conclusion: The Service Learning method is effective in improving the knowledge and attitude of pre-disaster preparedness of students in the Undergraduate Midwifery Study Program.